Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.26735/16586794.2017.019
|View full text |Cite
|
Sign up to set email alerts
|

Radio-morphometric Analysis of Sella Turcica in the South Indian Population: A Digital Cephalometric Study

Abstract: A higher percentage of both males (70.0%) and females (67.7%) were presented with normal sella. The second best sella presentation was the shallow sella in males (16.2%). The mean antero-posterior diameter was higher in females (12.25 mm) than males (11.74 mm). The mean depth of sella turcica was greater in females (8.08 mm) than males (7.68 mm). Discriminant function analysis was done with gender as a grouping variable and antero-posterior dimensions and sella depth as independent variables. The formula obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…Unlike our results; in Indian population, Sella depth attains the highest overall accuracy (56.9%) in univariate discriminant analysis followed by APD (53.9%) (Subasree and Dharman, 2019). In another Indian study; multivariate discriminant analysis, using only (Sella APD and depth) as independent variables, revealed that the overall accuracy was (58.1%) with higher sensibility in Indian females (58.5%) than Indian males (57.7%) (Kiran et al, 2017). In the current study multivariate discriminant analysis achieved over all accuracy of (52.7%) with higher sensibility in Egyptian males (67.6%) compared to Egyptian females (37.8 %).…”
Section: Discussioncontrasting
confidence: 93%
“…Unlike our results; in Indian population, Sella depth attains the highest overall accuracy (56.9%) in univariate discriminant analysis followed by APD (53.9%) (Subasree and Dharman, 2019). In another Indian study; multivariate discriminant analysis, using only (Sella APD and depth) as independent variables, revealed that the overall accuracy was (58.1%) with higher sensibility in Indian females (58.5%) than Indian males (57.7%) (Kiran et al, 2017). In the current study multivariate discriminant analysis achieved over all accuracy of (52.7%) with higher sensibility in Egyptian males (67.6%) compared to Egyptian females (37.8 %).…”
Section: Discussioncontrasting
confidence: 93%